Crime Days Precursors Study: Baltimore, 1952-1976 - Nurco, David ([Verlag nicht ermittelbar], 1985)
This data collection focuses on 354 male narcotic addicts who were selected using a stratified random sample from a population of 6,149 known narcotic abusers arrested or identified by the Baltimore, Maryland, Police Department between 1952 and 1976. Variables include respondent's use of controlled drugs, including marijuana, hallucinogens, amphetamines, barbiturates, codeine, heroin, methadone, cocaine, tranquilizers, and other narcotics. Also of interest is the respondent's past criminal activity including arrests, length of incarceration, educational attainment, employment history, personal income, mobility, and drug treatment, if any.